Early stages of periphrastic passive formation in Old Swedish - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2024)
This article discusses the construction [SBJ varda PTCP], which is considered an early example of a periphrastic passive, in the extant Old Swedish legal texts. It has been argued that it is a nascent passive construction, different from the fully-fledged passive in Present Day Swedish. Based on a corpus study of all occurrences of the construction across Swedish provincial laws I argue that it bears all the hallmarks of a grammaticalized passive construction, with two exceptions. Firstly, it allows a wider choice of thematic roles of the subject, secondly, its main pragmatic function is inactivization in the sense of Haspelmath (1990). The study is grounded in Diachronic Construction Grammar and utilizes the typology of thematic roles proposed by Van Valin and LaPolla (1997).